THE EFFECT OF TWIN DATE PROMOS, LIVE TIKTOK SHOP, AND FREE SHIPPING ON THE CONSUMPTIVE BEHAVIOR OF SKINTIFIC MAKEUP PRODUCTS - Putri, Nabhila Maharani Cahya; Santoso, Ety Dwi (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of digital marketing strategies—namely double date promotions, TikTok Shop live streams, and free shipping—on consumers’ consumptive behavior toward Skintific makeup products. The study is grounded in the context of shifting shopping patterns influenced by the rapid growth of digital technology, particularly in the beauty industry. Employing a quantitative approach with an associative method, data were collected through questionnaires distributed to 100 respondents who had purchased Skintific products via TikTok Shop. The data were analyzed using multiple linear regression to assess both the individual and combined impact of the three promotional variables on consumer behavior. The findings reveal that each of the three strategies, as well as their combined application, significantly influence consumer buying tendencies. These results suggest that the integration of digital promotions with interactive social media platforms plays a crucial role in stimulating purchasing behavior, especially among beauty product consumers. This research is expected to provide valuable insights for businesses in crafting more impactful and sustainable marketing strategies.